2018
DOI: 10.1159/000486411
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous β-Hydroxybutyrate Treatment and Neuroprotection in a Suckling Rat Model of Hypoxic-Ischemic Encephalopathy

Abstract: β-Hydroxybutyrate (BHB) is a representative ketone body that may play a role in the mitigation of neonatal hypoxic-ischemic encephalopathy by altering energy metabolism. This study aimed to investigate the neuroprotective efficacy of exogenous BHB administration in a suckling rat model after hypoxia-ischemia (HI). Thirteen-day-old (P13) rat pups were subjected to 120 min of hypoxia according to the Rice-Vannucci model. BHB (5.0 mmol/kg, HI-BHB) or vehicle (0.9% saline, HI-Veh) was administered 0, 2, 4, and 6 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 44 publications
1
20
0
Order By: Relevance
“…4). Initially thought of as a passive carrier of energy, BHB has proven to be an important signaling molecule in a variety of processes including neuroprotection and anti-inflammatory responses 34,3739 .
Figure 4Systemic levels of β-hydroxybutyric acid are significantly decreased post-cranial irradiation. ( A ) Systemic levels of β-hydroxybutyric acid 2 days (top) or 2 weeks (bottom) post 9 Gy cranial irradiation.
…”
Section: Resultsmentioning
confidence: 99%
“…4). Initially thought of as a passive carrier of energy, BHB has proven to be an important signaling molecule in a variety of processes including neuroprotection and anti-inflammatory responses 34,3739 .
Figure 4Systemic levels of β-hydroxybutyric acid are significantly decreased post-cranial irradiation. ( A ) Systemic levels of β-hydroxybutyric acid 2 days (top) or 2 weeks (bottom) post 9 Gy cranial irradiation.
…”
Section: Resultsmentioning
confidence: 99%
“…injection of b-OHB during an ischemic attack of the brain can provide favorable effects on brain function 30 days after the b-OHB administration. 51 Another study also reported that 6-hour continuous infusion of b-OHB ameliorated spinal cord injury 2 weeks after the treatment, which is concomitant with the increased H3K9 acetylation of the spinal tissues. 52 It can be of interest to examine the longer-term remote effects than in the present study, especially the progression to chronic renal damages after IR injury in this model several days after the termination of b-OHB treatment.…”
Section: The Effects Of Foxo3 Knockdown On B-ohb Mediated Anti-pyroptmentioning
confidence: 93%
“…11 Ketone bodies (acetone, acetoacetate, β-hydroxybutyrate) are efficiently transported into the brain where they serve as an alternative fuel source for oxidative metabolism (Ruderman et al , 1974). Exogenous administration of β-hydroxybutyrate in a rodent model of neonatal HIE decreased neurological injury (Lee et al , 2018a). In the same “Rice-Vannucci” model, Takenouchi et al (2015) showed that hypothermia decreased β-hydroxybutyrate and acetyl-CoA levels in the brain.…”
Section: The Csh Response During Cold Stress: Potential Applications mentioning
confidence: 99%
“…Total calorie content was equivalent in mice fed a ketogenic versus standard diet, indicating that the induction of UMH, and increased CIRBP expression, was not due to caloric restriction. Exogenous administration of ketones, in some models, improves histological outcomes after an acute brain injury and decreases neuropathology/cognitive impairment in chronic neurodegenerative disease (Kashiwaya et al , 2013; Pawlosky et al , 2017; Lee et al , 2018a). It is unclear if neuronal CIRBP levels might be increased by administration of ketones in the setting of brain injury, and if it influences recovery (i.e., direct CIRBP-mediated neuroprotective effects versus harmful activation of proinflammatory microglia).…”
Section: Induction Of Csps During Cold Stress: Potential Applicationsmentioning
confidence: 99%